Facile Synthesis of Corn Silk Derived Nanoporous Carbon for an Improved Supercapacitor Performance. Issue 14 (27th October 2018) - Mitravinda, Tadepalli; Nanaji, Katchala; Anandan, Srinivasan; Jyothirmayi, Adduru; Chakravadhanula, Venkata Sai Kiran; Sharma, Chandra Shekhar; Rao, Tata Narasinga
Abstract : Efforts made in this current study focus on the development of a novel, simple, cost-effective yet efficient approach to synthesize nanoporous carbon material from corn silk biomass for supercapacitor applications. We have employed different activation approaches in order to obtain a higher surface area and large mesoporous volume fraction. The performance of corn silks derived nanoporous activated carbon materials for supercapacitor applications was evaluated in a symmetric two electrode configuration using aqueous/non-aqueous electrolytes at various current densities and scan rates. Electrochemical results indicated that the as-synthesized nanoporous carbon prepared by single step activation exhibits ideal supercapacitor performance ∼160 F/g (at 1 A/g current density) with excellent rate capability and cyclic stability. Further, it displayed a promising amount of energy that can be stored in a given mass ∼32.28 Wh/kg at the power density of 870.68 W/kg. Benchmark studies revealed that the nanoporous carbon developed in the current study is at par with the performance of the commercial carbon electrode. The superior performance of corn silks derived nanoporous carbon is attributed to high surface area pertaining to its unique mesoporous fiber-like morphology, which facilitates fast ionic and electronic diffusion of the electrolyte into and out of the pores during charging and discharging.